Records of the Department of State relating to internal affairs of Mexico, 1910-29 (National Archives microfilm publications ;)
Contains records from the Dept. of State decimal file 812, mostly instructions to and despatches from diplomatic and consular officials. The largest group of records deals chiefly with the Mexican Revolution.